PERAN BUDAYA ORGANISASI DALAM MEMBENTUK PERILAKU POSITIF ANGGOTA PADA PR IPNU-IPPNU DESA BALONGGABUS KECAMATAN CANDI KABUPATEN SIDOARJO - Lailatul Zahra; Wahyu Eko Pujianto (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Youth organizations play an important role in shaping the character and positive behavior of young people through the implementation of sustainable organizational culture. One of these organizations is the Branch Leadership (PR) of IPNU-IPPNU in Balonggabus Village, Candi District, Sidoarjo Regency. This study aims to analyze the role of organizational culture in shaping the positive behavior of members of PR IPNU-IPPNU Balonggabus Village. This research employed a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation, and analyzed using the Miles, Huberman, and Saldaña model, which includes data condensation, data display, and conclusion drawing. The findings reveal that organizational culture is implemented through cadre development activities, such as Masa Kesetiaan Anggota (MAKESTA) and Latihan Kader Muda (LAKMUD), as well as religious and social activities, including Qur'an recitation, Diba'an, Islamic holiday commemorations, and community service. These organizational activities contribute to the development of members' positive behavior, reflected in improved discipline, responsibility, teamwork, leadership, and social awareness. Therefore, organizational culture serves as an essential factor in shaping members' character while strengthening the sustainability of youth organizations as a medium for developing future generations.